2018
DOI: 10.5194/acp-2018-482
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A new interpretative framework for below-cloud effects on stable water isotopes in vapour and rain

Abstract: Abstract. Raindrops interact with water vapour in ambient air while sedimenting from the cloud base to the ground. They constantly exchange water molecules with the environment and, in sub-saturated air, they evaporate partially or entirely. The latter of these below-cloud processes is important for predicting the resulting surface rainfall amount and it influences the boundary layer profiles of temperature and moisture through to evaporative latent cooling and humidity changes. However, despite its importance… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 20 publications
4
46
1
Order By: Relevance
“…For example, precipitation from high d vapor, from continental recycling or rapid evaporation from the ocean that experiences subcloud evaporation may not exhibit very low d , whereas low d vapor, such as vapor from a humid, cool oceanic boundary layer may exhibit less subcloud evaporation but produce the same d . However, the range of seasonal average d observed in our data set matches the range of d from three studies (Chen et al, ; Graf et al, ; Wang et al, ) that measured precipitation isotope ratios and modeled a strong contribution of subcloud evaporation to the observed d .…”
Section: Resultssupporting
confidence: 87%
“…For example, precipitation from high d vapor, from continental recycling or rapid evaporation from the ocean that experiences subcloud evaporation may not exhibit very low d , whereas low d vapor, such as vapor from a humid, cool oceanic boundary layer may exhibit less subcloud evaporation but produce the same d . However, the range of seasonal average d observed in our data set matches the range of d from three studies (Chen et al, ; Graf et al, ; Wang et al, ) that measured precipitation isotope ratios and modeled a strong contribution of subcloud evaporation to the observed d .…”
Section: Resultssupporting
confidence: 87%
“…Data availability. All observation data presented in this study are openly available from the ETH Research Collection at https://doi.org/10.3929/ethz-b-000271617 (Graf et al, 2018). P. Graf et al: Below-cloud effects on stable water isotopes been implemented: Growth by vapour deposition in mixedphase or ice clouds, and riming of liquid cloud droplets on frozen particles.…”
Section: Discussionmentioning
confidence: 99%
“…These variations integrate all processes along air mass trajectories (Figure 4, blue dashed square). The third term (Figure 4, magenta dashed square) represents a combination of precipitation‐vapor disequilibrium effects (due to variations in condensation altitude or postcondensation processes such as rain evaporation), variations in the vertical gradients between the surface (where the precipitation achieves its last equilibration, e.g., Graf et al, 2019) and 5 km (where the water vapor δ 2 H is observed by IASI) and small‐scale variations in water vapor δ 2 H (leading to difference between the water vapor δ 2 H observed by IASI and that with which the precipitation locally equilibrates).…”
Section: Methodsmentioning
confidence: 99%